Music, Language, and Autism: Neurological Insights for Enhanced Learning - Luo, Emanuel; Pan, William; Fan, Xiujun (International Journal of Innovative Research in Medical Science, 2023)
This comprehensive review thoroughly explores the intricate relationship between music and language, encompassing their historical, cognitive, and neural dimensions. It draws evidence from ancient Chinese civilizations dating back to 4500 BC to analyze the coexistence and parallel evolution of music and language for the first time. Comparative studies illuminate the shared and distinctive aspects of pitch, rhythm, and syntax inherent to music and language. The examination extends to the diverse impact of music, including second language acquisition, phonological awareness, pitch processing, memory, and cognitive skills. This influence is also observed among individuals with Autism Spectrum Disorder. The paper further examines the intricate neural connections, neural overlapping, networks, structural processing, bidirectional relationships, cross-modal transfer effects, and brain plasticity that underpin music and language. It reviews music interventions for enhancing language and cognitive abilities, particularly in the context of autism spectrum disorders. However, the precise role of music and its intricate neural mechanisms in shaping language-related outcomes within Autism spectrum disorder groups remains incompletely understood. Further interdisciplinary research integrating disciplines like neuroscience, psychology, sociology, and related fields is imperative to deepen our comprehension and unlock the precise neural mechanisms and interventions that can foster enhanced language and cognitive development in individuals with autism.